THE INFLUENCE OF SELF-REGULATED LEARNING AND ACADEMIC BOUYANCY ON SCHOOL ADJUSTMENT OF STUDENTS AT THE AN-NUR ISLAMIC BOARDING SCHOOL TANGGULANGIN - Faridatul Amailiyah; Ghozali Rusyid Affandi (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2023)
School adjustment is a phenomenon that is often found in schools with a boarding school basis. It is assumed that the factor that influences students' school adjustment is self-regulated learning and another factor is their academic buoyancy. The purpose of this study was to determine the effect of self-regulated learning and academic buoyancy on school adjustment among students at the An-nur Islamic boarding school. The participants in this study were all students at the An-Nur Islamic boarding school, totaling 195 students. The data collection technique uses 3 psychological scales, namely academic buoyancy with a value of (α) = 0.523, self-regulated learning with a value of (α) = 0.815 and school adjustment with a value of (α) = 0.918 The data analysis technique uses multiple linear regression analysis techniques with the help of SPSS26.0 for windows. The results of the study show that self-regulated learning and academic buoyancy positively influence school adjustment for students at the An-nur Islamic boarding school. the influence exerted by academic bouyancy and self-regulated learning on school adjustment is only 39%, while 61% of other factors are not found in this study.